2021
DOI: 10.1021/acsomega.1c01729
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulations of the Influence of Inert Gases (N2/CO2) on Combustion Characteristics of Laminar-Premixed Biosyngas Flame

Abstract: In this work, the influence of different N2/CO2 contents (up to 60% in fuel volume) on combustion features of laminar-premixed CO/CH4/H2 flame with various equivalence ratios (0.6–1.6) at standard conditions was numerically calculated using ANSYS CHEMKIN-PRO with the GRI-Mech 3.0 mechanism. The mole fraction profiles of the major species and the rate of production of dominant elementary reactions in the flames of CO/CH4/H2/N2/CO2/air were obtained. The effect of inert gas addition on the formation of NO X , H,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Assuming that the gas inlet is a one-dimensional steady flow, the governing equation can be simplified as follows (Kuo, 2005;Sun et al, 2021):…”
Section: Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…Assuming that the gas inlet is a one-dimensional steady flow, the governing equation can be simplified as follows (Kuo, 2005;Sun et al, 2021):…”
Section: Mechanismmentioning
confidence: 99%
“…The results showed that the laminar flame speed has a good positive correlation with the adiabatic temperature under different equivalent ratios. The inhibition effect of CO 2 is stronger than N 2 , which may be related to the chemical effect and heat capacity of CO 2 (Sun et al, 2021). It can be seen from the above that the change of CO 2 concentration has a stronger influence on combustion characteristics than N 2 , and most scholars have studied the influence of inert gas on combustion characteristics of simple components (methane, methane-air mixture, etc.).…”
Section: Introductionmentioning
confidence: 97%
“…Therefore, in this study, an electrohydraulic proportional control valve was selected as the research object, and an advanced international reversing valve was selected as the reference object [27][28][29][30][31]. A mathematical model of the pressure compensation system was established using the power bond diagram method.…”
Section: Introductionmentioning
confidence: 99%
“…Investigations on the effects of different inert gas dilutions on the combustion processes have been conducted, which illustrates that the dilution of inert gas has distinctive influences on the energy deposition and the kinetic coefficient of methane–air plasma in the ignition process. In addition, Yi et al have indicated that different diluent concentrations have a significant impact on the flame structure and the soot flame temperature . Mohammad et al have proved that the burning velocity decreases with the increase in percentage of inert gas .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Ar and He are suitable feed gases for the research of the effect of inert gas dilution on the methane–air PAI due to their easy acquisition and low cost. Sun et al and Liu et al have conducted studies on combustion characteristics, the results of which showed that the addition of inert gases like N 2 /CO 2 or Ar to the fuel mixture can appropriately control the flame temperature and the species generated from He-diluted fuel has lower oxidation reactivity. , Zhang et al have pointed out that the dilution of Ar not only can keep the cycle-by-cycle variations of the tested engine unchanged but also is beneficial for the mean effective pressure . Since the inert gas dilution has significant influences on the PAC and Ar and He are the general and appropriate inert gases, the present study takes the inert gases Ar and He into account.…”
Section: Introductionmentioning
confidence: 99%